Do plasmids containing heavy metal resistance genes play a role in neonatal sepsis and invasive disease caused by Klebsiella pneumoniae and Klebsiella variicola?. Issue 8 (16th August 2022) - Turton, Jane F.; Perry, Claire; Claxton, Alleyna
Abstract : Introduction. Klebsiella species are some of those most implicated in neonatal sepsis. However, many isolates from infections appear unremarkable; they are generally susceptible to antibiotics and often of sporadic types not associated with virulence. Hypothesis/Gap Statement. Investigation is needed to identify if such isolates have virulence characteristics. Aim. To sequence multiple isolates of a range of types from cases of neonatal invasive disease to identify elements that may explain their virulence, and to determine if such elements are more common among these isolates than generally. Methodology. In total, 14 isolates of K. pneumoniae / K. variicola belonging to 13 distinct types from blood or CSF from neonatal infections were sequenced using long-read nanopore technology. PCR assays were used to screen a general set of isolates for heavy metal resistance genes arsC, silS and merR . Results. Overall, 12/14 isolates carried one or more plasmids. Ten carried a large plasmid (186 to 310 kb) containing heavy metal resistance genes associated with hypervirulence plasmids, with most (nine) carrying genes for resistance to copper, silver and one other heavy metal (arsenic, tellurite or mercury), but lacking the genes encoding capsule-upregulation and siderophores. Most isolates (9/14) lacked any additional antibiotic resistance genes other than those intrinsic in the species. However, a representative of an outbreak strain carried a plasmid containing bla CTX-M-15, qnrS1, aac3 _IIa, dfrA17, sul1, mph(A ), tet(A ), bla TEM1B and aadA5, but no heavy metal resistance genes. arsC, silS and merR were widely found among 100 further isolates screened, with most carbapenemase-gene-positive isolates (20/27) carrying at least one. Conclusion. Plasmids containing heavy metal resistance genes were a striking feature of isolates from neonatal sepsis but are widely found. They share elements in common with virulence and antibiotic resistance plasmids, perhaps providing a basis from which such plasmids evolve.